Inducing AC-electroosmotic flow using electric field manipulation with insulators. Issue 16 (13th July 2021) - Tiflidis, C.; Westerbeek, Eiko Y.; Jorissen, Koen F. A.; Olthuis, Wouter; Eijkel, Jan C. T.; De Malsche, Wim
Abstract : We demonstrate a new method to induce vortices with AC-EOF by shaping insulator materials near parallel electrodes, giving control of vortex organization. Interestingly, non-orthogonality of insulator walls is a requirement to induce AC-EOF. Abstract : Classically, the configuration of electrodes (conductors) is used as a means to determine AC-electroosmotic flow patterns. In this paper, we use the configuration of insulator materials to achieve AC-electroosmotic flow patterning in a novel approach. We apply AC electric fields between parallel electrodes situated on the top and bottom of a microfluidic channel and separated by an insulating material. Channels of various cross-sectional shapes ( e.g. rectangular and parallelogram) were fabricated by shaping the insulating material between the electrodes. We found that vortex flow patterns are induced depending on the cross-sectional shape of the channel. A bell-shaped design with non-orthogonal corners gave rise to 2 vortices, whereas in a channel with a parallelogram shaped cross-section, only a single vortex was observed. The vortices were experimentally observed by analysing the 3D trajectories of fluorescent microparticles. From a theoretical analysis, we conclude that flow shaping is primarily caused by shaping the electrical field lines in the channel.